Analisis Risiko Usahatani Kelapa Sawit di Kecamatan Lariang Kabupaten Mamuju Utara - Mulaputri, Sitti Hardiyanti; Demmallino, Eymal B.; Saadah (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2023)
The need for risk analysis is caused by the farmers who often face the problem of uncertain farming profits. The limitation of farmers causes it to control the climate and the market price. This uncertainty causes the risk of production and income which will influence the farmer's profits. This research aims to know the risk of production and income and also to know the ways farmers mitigate the risk. This research was conducted in Lariang, North Mamuju Regency. The research location was chosen by using Purposive Sampling. The time of the research was from May to July. The respondent sample was chosen by using Simple Random Sampling with a total response of 32 samples. The data analysis method used income analysis, coefficient variation analysis (CV), and descriptive analysis. The result of this research showed the average farmer's income in Lariang was 23.866.632,-/Ha/Year. Risk of production with a coefficient variation (CV) of 0.034 it was found that palm farming in Lariang was in low-risk production and income. The way that can be used by the farmers to mitigate the risk of production is to provide appropriate potions to overcome pests and provide fertilizer stock. Mitigating the risk of income is that the farmers should pay more attention to the harvest moon, fruit transport, and also TBS quality to earn high sales.